Kaddish : women's voices - Smart, Michal; Ashkenas, Barbara (Urim Publications, 2013)
For centuries, Jews have turned to the Mourner's Kaddish prayer upon experiencing a loss. This groundbreaking book explores what the recitation of Kaddish has meant specifically to women. Did they find the consolation, closure, and community they were seeking? How did saying Kaddish affect their relationships with God, with prayer, with the deceased, and with the living? With courage and generosity, 52 authors from around the world reflect upon their experiences of mourning. They share their relationships with the family members they lost and what it meant to move on; how they struggled to balance the competing demands of child rearing, work, and grief; what they learned about tradition and themselves; and the disappointments and particular challenges they confronted as women.